Quasi Random Deployment and Localization in Layered Framework for the Internet of Things. (14th April 2017) - Pandey, Saurabh K; Zaveri, Mukesh A
Abstract: Real-time information access and service delivery are very crucial for handling different events and providing the quick response for different applications. These tasks can be achieved through the network of devices which enables the device-to-device communication. Internet of Things is a realization of such kind of network. The advantage of Internet of Things is that it allows us to access device at anytime and from anywhere. It directs us to provide not only location aware services but also poses a need to have better network coverage for performing a specific task using the network of devices. Location information and proper deployment of devices are very important for effective utilization of Internet of Things for a given application. In this context, two fundamental tasks, i.e. efficient deployment of devices followed by the issue of location estimation of these devices need to be addressed on priority. For this reason, in this paper, we propose two algorithms; for efficient deployment of the devices and for location estimation of these devices, respectively. For deployment, we explore quasi-random strategy and for location estimation, we consider received signal strength indicator-based approach. The proposed methods are compared with existing techniques to prove its efficacy in Internet of Things environment.